«Vogliatemi bene»: lettere di Matilde Serao a Gabriele d’Annunzio - Trevisan, Alessandra (Archivio d’Annunzio, 2019)
Between ca. 1885 and 1927, Gabriele d’Annunzio and Matilde Serao became friends and contributed to journals in Rome and Naples; they met authors in Europe (especially in France), exchanged opinions about their works and also about their private life. She has been a vibrant constant on Vate’s experience: she gave him advices and protected his affair with Eleonora Duse, who was also Matilde’s friend. Serao’s collection of letters, kept by Fondazione Il Vittoriale degli Italiani in Gardone Riviera, explains some contours of a crucial friendship.